ANALISIS TRADING DAY, TRADING VOLUME, DAN TRADING FRECUENCY TERHADAP RETURN SAHAM PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Margha Rettha Ayu Chornelia; Dwi Suhartini (Jurnal Akuntansi dan Keuangan (JAK), 2020)
This study aims to analyze the trading day, trading volume, and frequency trading of stock returns on food and beverage companies listed on the Indonesia Stock Exchange for the period of 2016- 2018. This research method uses a quantitative approach. The analytical method used in this study is multiple regression with the help of the SPSS program. Data sources in this study are secondary data sources obtained through the official website of the Indonesia Stock Exchange. The population and sample of this study were 54 populations and 41 samples. The sampling technique uses non probability sampling that is taking a sample with consideration of certain criteria. The variables used in this study are Trading Day, Trading Volume, and Trading Frequency as an independent variable and Stock Return as the dependent variable. The results of this study indicate that trading day has no effect on stock returns, trading volume has a positive influence on stock returns, and trading frequency has a negative effect on stock retur